A Clinical Study of Allergy and COPD Correlation With Spirometric and FENO Evaluation - Dange, Hemalata; Patil, Rupali; Upasani, Chandrashekhar (International Journal of Experimental Research and Review, 2023)
Occurrence of allergies & asthma increased in India and may be the top public health concern. The risk of allergies and other allergic diseases might grow with on-going exposure to allergens. There are various unusual allergies, including natural rubber latex, pollen, dust, medications (including antibiotics), food, fungus spores, insect and mite excrement, insect bites and stings (and their venom). The not unusual allergens which might be chargeable for respiratory troubles have been diagnosed after a sincere attempt. A take-look study was conducted on one hundred fifteen patients to assess hypersensitivity and COPD correlation. Their medical histories have been accrued to examine whether or not they were exposed to unique allergens or no longer in the past. All the individuals underwent a Skin Prick Test (SPT) with selected allergens to assess allergens exposure. Patient's Spirometry and FENO check statistics were collected for COPD prognosis. Most COPD patients showed mild to extreme allergic reactions to various allergens.